The Eco-Hero in Malaysian Novels: from solitary figures to group solidarity - Zainal, Zainor Izat (Palgrave Macmillan, 2024)
This chapter is informed by Tim (Poland, Western American Literature 26:195–208, 1991) concept of the “eco-hero”, who “seeks and nurtures diversity and complexity and fights against all forms of pollution, class hierarchy and outside threats to bioregional autonomy”, thus rejecting self-interest in search for the “ecocentric Self” (p. 197). Here, I analyse eco-heroes in five contemporary eco-centred Malaysian novels: Keris Mas’s Jungle of Hope (2009), Zakaria Ali’s The Dam (2009), Yang-May Ooi’s The Flame Tree (1998), K.S. Maniam’s Between Lives (2003) and Chuah Guat Eng’s Days of Change (2010). Although the environmental complexities presented in these works differ, their common narrative thread is representing grassroots struggles against environmental degradation in Malaysia, spanning colonial rule to the present time. This chapter thus aims to answer two pertinent questions: (1) how successful are these fictional eco-heroes in their quest to fight environmental threats; and (2) what characterises their successes and failures? I argue that an understanding of the history of local environmentalism influences the successes and failures of these fictional eco-heroes and posit that the conception of the eco-hero has transformed from that of a solitary figure to an expression of group solidarity in the Malaysian context.